Midline neck swelling mimicking thyroglossal CYST: Report of an uncommon presentation of cysticercous infestatation - Bundela, Tanuja; Gupta, Prajwala; Bhardwaj, Minakshi (Indian Journal of Case Reports, 2019)
Cysticercosis in humans is caused by an infestation by larvae of Taenia solium. The neck is a rare site of the infestation. Here, we present the case of cysticercosis situated in the neck of a 12-years-old child. The midline neck swelling present in the child since 2 years mimicked thyroglossal cyst, both clinically and radiologically. There were no other systemic complaints. Fine Needle Aspiration Cytology (FNAC) of the swelling was done for reaching the final diagnosis. Hence, in all inflammatory/cystic lesions, particularly in endemic areas, the possibility of cysticercosis should be taken into consideration irrespective of age, location, and the size of the lesion.